Pengembangan LKS dengan Model Discovery Learning pada Materi Irisan Dua Lingkaran - Harisman Nizar; Somakim Somakim; Muhammad Yusuf (Jurnal Elemen, 2016)
This research aims at (1)producing a valid and practical LKS (Student Worksheet) in discovery learning model in two circles intersection material in class XI, and (2) to find out the potential effect toward the learning outcomes from the development of LKS with discovery learning model in two circles intersections material in class XI MIA. The design ofthis research is a developmental study. The subjects of this research were 33 students of XI MIA 1 SMA N 1 Indralaya in academic year 2015/2016. The data collecting technique used were observation, test, and interview. The result of the researches were : (1) This research produced a valid and practical LKS with discovery learning model in two circles intersections material in class XI MIA withsome characteristics such as, (a) Contain the operational steps of discovery learning model, (b) Help students in finding the concept of two circles intersections model. (c) Make students active in learning. Being valid can be seen from the results of validator assessment, where the validator comments on the first prototype of LKS from content, construct, and language. Being practical can be seen from the results of  small group try out, in which it was based on analysis of the answer sheets of students, it was found that students were able to complete each steps there and studentsâ€™ comments obtained from the sheets that stated the LKS given was easy to be done by students. (2) The developed LKS consisted of potential effect toward the learning outcomes from cognitive (knowledge), affective (attitude), and psychomotor (skill). In the cognitive domain 81.81% of students got score 65, in the affective domain all of the students had shown an attitude of honesty and responsiveness shown by observations during LKS usage, as well as in the of psychomotor domain skills all of students had good skill that seen from the result of students performance.